IMPLEMENTASI ALGORITMA TWOFISH DANI LEAST SIGNIFICANT BIT (LSB) UNTUK PENYEMBUNYIAN FILE TEXT PADA CITRA DIGITAL - Devri Riza Setyawan; Willy Sudiarto Rahardjo; R. Gunawan Santosa (Universitas Kristen Duta Wacana, 2015)
Security and confidentiality of information are considered a requirement in today's communication media. Many people have used Internet to share and distribute confidential information. On the other hand, many malicious activities attempts to steal those information by irresponsible parties. Therefore, information must be secured and converted into another form before it is sent to the destination by the use of cryptography and steganography. We developed a program to secure this information, by using Twofish and Least Significant Bit algorithm to encrypt secret messages and then insert it into an image file. By combining these two methods, we can achieve higher levet of information security.The information encoded with twofish algorithm will change the fite size stightly. This changes are caused by the use of padding. In addition, both of the output image are not resistant by some manipulation operations. The output of the system in BMP format does not change the file size after insertion process, while PNG format will have a stightty dffirence infile size due to processing in bitmap mode.